Affectively effective: Work-related emotional intelligence as a predictor of organizational citizenship - Robinson, Michael D.; Irvin, Roberta L.; Krishnakumar, Sukumarakurup (Frontiers in Psychology, 2023)
Efforts to link ability-related emotional intelligence to organizational behavior have resulted in modest findings. The present three studies examine whether a work-contextualized form of emotional intelligence (W-EI) may have greater predictive value, particularly in the organizational citizenship domain. Because W-EI should benefit social relationships within the workplace, positive associations between W-EI and organizational citizenship behavior were hypothesized. This hypothesis was supported in three studies (total N = 462) involving samples of part-time student employees (Study 1), postdoctoral researchers (Study 2), and full-time employees (Study 3). All studies also provided evidence for incremental validity, such as with respect to the Big 5 personality traits, and Study 3 highlighted processes related to workplace engagement (in the form of higher levels of interpersonal job satisfaction and lower levels of burnout). The results demonstrate the importance of W-EI in understanding employee variations in organizational citizenship.